2021
DOI: 10.1002/ijgo.13912
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian function following use of various hemostatic techniques during treatment for unilateral endometrioma: A randomized controlled trial

Abstract: Objective To compare the effect of hemostatic techniques (bipolar energy versus hemostatic sealants versus suture) on the ovarian reserve of patients submitted to laparoscopic cystectomy for the surgical excision of unilateral endometrioma. Methods A randomized controlled trial conducted in a teaching hospital included 84 patients with unilateral endometrioma. The patients underwent laparoscopic stripping for excision of the unilateral endometrioma between March 2018 and February 2020. Three different hemostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Lower rates of spontaneous pregnancy and higher rates of recurrence are associated with ablative surgery compared with cystectomy, whereas cystectomy was found to be deleterious for residual ovarian function (162,379,380). Since the meta-analysis of Dan et al in 2013 (380), RCTs comparing ablative versus excisional techniques in terms of ovarian reserve markers and ovarian residual volume have been performed (381)(382)(383)(384)(385)(386). Data from animal studies (387) and RCT (381,382,388) on the use of laser and plasma energy is encouraging and may result in less inadvertent tissue removal and thermal injury compared with cystectomy and bipolar electrosurgery.…”
Section: Fertility Sparing Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Lower rates of spontaneous pregnancy and higher rates of recurrence are associated with ablative surgery compared with cystectomy, whereas cystectomy was found to be deleterious for residual ovarian function (162,379,380). Since the meta-analysis of Dan et al in 2013 (380), RCTs comparing ablative versus excisional techniques in terms of ovarian reserve markers and ovarian residual volume have been performed (381)(382)(383)(384)(385)(386). Data from animal studies (387) and RCT (381,382,388) on the use of laser and plasma energy is encouraging and may result in less inadvertent tissue removal and thermal injury compared with cystectomy and bipolar electrosurgery.…”
Section: Fertility Sparing Surgerymentioning
confidence: 99%
“…Since the meta-analysis of Dan et al. in 2013 ( 380 ), RCTs comparing ablative versus excisional techniques in terms of ovarian reserve markers and ovarian residual volume have been performed ( 381 386 ). Data from animal studies ( 387 ) and RCT ( 381 , 382 , 388 ) on the use of laser and plasma energy is encouraging and may result in less inadvertent tissue removal and thermal injury compared with cystectomy and bipolar electrosurgery.…”
Section: Management Of Endometriosis Associated Infertilitymentioning
confidence: 99%
“… 31 In contrast, twelve publications were identified from classic trials started after 2018, mainly involving gonadotropin-releasing hormone receptor antagonists, 32 , 33 pre- in vitro fertilization (IVF) medication, 34 surgery, and ovarian function preservation. 35 …”
Section: Resultsmentioning
confidence: 99%
“…However, two studies reported significantly smaller serum AMH decrements in the suturing group [ 20 , 21 ]. Among the six studies comparing bipolar coagulation versus hemostatic agent, the serum AMH decrements were similar in three studies [ 22 , 23 , 24 ]. However, three studies reported significantly smaller serum AMH decrements in the hemostatic agent group [ 16 , 25 , 26 ].…”
Section: Ovarian Cystectomymentioning
confidence: 99%
“…Interestingly, Araujo et al [ 24 ] compared serum AMH decrements after all three methods (bipolar coagulation versus suturing versus a hemostatic agent), but the serum AMH decrements were similar in all groups. These 11 studies showed varying results for the results of the serum AMH decrement; therefore, no conclusions can be drawn.…”
Section: Ovarian Cystectomymentioning
confidence: 99%